2020
DOI: 10.1007/s10389-020-01279-y
|View full text |Cite
|
Sign up to set email alerts
|

On the global trends and spread of the COVID-19 outbreak: preliminary assessment of the potential relation between location-specific temperature and UV index

Abstract: The novel coronavirus, since its first outbreak in December, has, up till now, affected approximately 114,542 people across 115 countries. Many international agencies are devoting efforts to enhance the understanding of the evolving COVID-19 outbreak on an international level, its influences, and preparedness. At present, COVID-19 appears to affect individuals through person-toperson means, like other commonly found cold or influenza viruses. It is widely known and acknowledged that viruses causing influenza p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 13 publications
9
70
1
1
Order By: Relevance
“…Some studies have suggested that temperatures in excess of 27 °C, ultra-violet rays associated with sunlight and humidity all tend to have negative effects on the survival of the virus. 18 We could not demonstrate this for African countries. However, the rise in numbers in the southern part of the continent currently experiencing their winter season and the relatively lower numbers and mortality in countries closer to the equator with higher temperatures and higher intensity of UV-light might be in keeping with these speculations.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Some studies have suggested that temperatures in excess of 27 °C, ultra-violet rays associated with sunlight and humidity all tend to have negative effects on the survival of the virus. 18 We could not demonstrate this for African countries. However, the rise in numbers in the southern part of the continent currently experiencing their winter season and the relatively lower numbers and mortality in countries closer to the equator with higher temperatures and higher intensity of UV-light might be in keeping with these speculations.…”
Section: Discussionmentioning
confidence: 73%
“…16 This source has also been used in previous studies on temperature and coronavirus cases. 17 , 18 The Human Development Index (HDI) data was retrieved from the United Nations Development Program (UNDP) 2019 Human development report. Flights data was accessed from the International Civil Aviation Organization, which publishes civil aviation statistics on air transport.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is necessary to consider comprehensive biophysical assessments of altitude, humidity, UV radiation in the maintenance and transmission of SARS-CoV-2. [9,10]. Recently studies have been published about temperature and UV index, and that heating, and UV irradiation can eliminate the viral infectivity [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…[9,10]. Recently studies have been published about temperature and UV index, and that heating, and UV irradiation can eliminate the viral infectivity [9,10]. These ndings could help to understand the relationship of COVID-19 cases in different cities Brazil due to altitude.…”
Section: Discussionmentioning
confidence: 99%
“…Our goal was to inquiry why the reported number of infections in Mexico is lower than expected based on population size and the aforementioned factors. We focused our discussion in a series of potential environmental factors that could be related with the lower rate of infections observed especially in Mexico City, as the solar UV irradiation (Sagripanti and Lyte 2007;Gunthe et al 2020), the ventilation of houses and public transport, and Mexican vaccination scheme. It is important to highlight a possible gap in epidemic statistics based in the low number of COVID-19 tests in relation to population size in Mexico (Theodoros et al 2020).…”
Section: Introductionmentioning
confidence: 99%